Ester Cross-Link Profiling of the Cutin Polymer of Wild-Type and Cutin Synthase Tomato Mutants Highlights Different Mechanisms of Polymerization. Issue 2 (16th December 2015) - Philippe, Glenn; Gaillard, Cédric; Petit, Johann; Geneix, Nathalie; Dalgalarrondo, Michèle; Bres, Cécile; Mauxion, Jean-Philippe; Franke, Rochus; Rothan, Christophe; Schreiber, Lukas; Marion, Didier; Bakan, Bénédicte
Abstract : A Synthase impacts ester cross-links of tomato cutin. Abstract: Cuticle function is closely related to the structure of the cutin polymer. However, the structure and formation of this hydrophobic polyester of glycerol and hydroxy/epoxy fatty acids has not been fully resolved. An apoplastic GDSL-lipase known as CUTIN SYNTHASE1 (CUS1) is required for cutin deposition in tomato ( Solanum lycopersicum ) fruit exocarp. In vitro, CUS1 catalyzes the self-transesterification of 2-monoacylglycerol of 9(10), 16-dihydroxyhexadecanoic acid, the major tomato cutin monomer. This reaction releases glycerol and leads to the formation of oligomers with the secondary hydroxyl group remaining nonesterified. To check this mechanism in planta, a benzyl etherification of nonesterified hydroxyl groups of glycerol and hydroxy fatty acids was performed within cutin. Remarkably, in addition to a significant decrease in cutin deposition, mid-chain hydroxyl esterification of the dihydroxyhexadecanoic acid was affected in tomato RNA interference and ethyl methanesulfonate- cus1 mutants. Furthermore, in these mutants, the esterification of both sn -1, 3 and sn -2 positions of glycerol was impacted, and their cutin contained a higher molar glycerol-to-dihydroxyhexadecanoic acid ratio. Therefore, in planta, CUS1 can catalyze the esterification of both primary and secondary alcohol groups of cutin monomers, and another enzymatic or nonenzymatic mechanism of polymerization may coexist with CUS1-catalyzed polymerization. This mechanism is poorly efficient with secondary alcohol groups and produces polyesters with lower molecular size. Confocal Raman imaging of benzyl etherified cutins showed that the polymerization is heterogenous at the fruit surface. Finally, by comparing tomato mutants either affected or not in cutin polymerization, we concluded that the level of cutin cross-linking had no significant impact on water permeance.